University consortium to address public health priorities and research capacity building in the Caribbean - Li, Allison; Lindo, John F.; Beckles, Hilary; Mohler, James L.; Reid, Marvin; Boyne, Michael; DeHovitz, Jack; Diaz, Patricia I.; Brown, Paul; Anzinger, Joshua; Carrington, Christine; Anderson, Kathryn B.; et al. (Frontiers in Education, 2023)
The State University of New York (SUNY) – University of the West Indies (UWI) Health Research Consortium (HRC) was implemented in 2015 by the SUNY Global Health Institute (GHI) and the SUNY-UWI Center for Leadership and Sustainable Development. The goal was to advance public health in the Caribbean through collaborative research and education among faculty and students at SUNY and UWI. The Consortium is now a dynamic matrix addressing health priorities that were initially agreed upon with the Jamaica Ministry of Health and Wellness. The HRC has built a foundational matrix that is planning for cutting edge laboratory instrumentation, biomedical informatics system, seamless electronic medical records network, national laboratory data management system, and novel biotechnology (e.g., robotic surgery cluster). The SUNY-UWI partnership fills existing gaps through collaborative programs with the SUNY GHI that facilitate UWI faculty interactions with SUNY faculty and core resources and incubators that encourage collaborations while UWI infrastructure expands. The Health Research Consortium utilizes existing academic models at UWI and SUNY to promote collaboration, capacity building, and program implementation. Consortium teams develop sound business development models that foster sustained economic growth and form the pipeline for workforce development and career opportunities. The Caribbean diaspora and UWI alumni are engaged in working together on this effort. In addition, mentoring in K-12 and beyond is needed to create a vision for the next generations.